Hip, Knee, and Ankle functional demand during habitual and fast-pace walking in younger and older women - Spinoso, Deborah Hebling [UNESP]; Marques, Nise Ribeiro; LaRoche, Dain Patrick; Hallal, Camilla Zamfollini; Karuka, Aline Harumi [UNESP]; Milanezi, Fernanda Cristina [UNESP]; Gonçalves, Mauro [UNESP] (Human Kinetics, 2019)
This study compared functional demand (FD) between older and younger women walking at habitual and fast speed and determined strength thresholds necessary to maintain FD below 80%. FD was calculated by expressing walking flexion and extension joint torques of the ankle, knee, and hip as a percentage of maximal strength. Young women had an average FD of 65% across joint actions and speeds, whereas older women had FD of 90%. In older women, the greatest FD occurred in the hip musculature. The hip, knee, and ankle extensor strengths required to maintain FD below 80% were 1.66, 1.86, and 0.57 Nm/kg, and flexor strengths were 1.24, 0.49, and 0.69 Nm/kg, respectively. Older women have limited functional reserve to increase gait speed and rely heavily on available hip strength during walking. This study identifies strength targets for the hip, knee, and ankle that will assist in maintaining FD of older women at a sustainable level.
Keywords: aging; falls; gait; mobility limitation; physical capacity